Potassium Solubilization By Indigenous Rhizobacteria Isolated From Saline Soil And Their Impact On Early Growth And Macronutrient Concentrations In Paddy Crop (Oryza Sativa L. Var. MRIA 1) - Ashfaq, Muhammad (2022)
Salinity is a major abiotic factor in soils that severely affects plant growth and continuously reduces the cultivated area. Under saline conditions, sodium is the most important cation, which is very harmful to plants. The potassium and sodium cations compete for their uptake in plants, primarily through High-Affinity Potassium Transporters and Nonselective Cation Channels. Microorganisms play a vital role in solubilizing fixed potassium and making it available to plants. In the present study, forty-two potassium solubilizing rhizobacteria were isolated from paddy fields in the coastal area of Kuala Muda, Malaysia. Thirteen strains from the isolated rhizobacteria were positive for phosphorus solubilization, Indole Acetic Acid (IAA), siderophores, ammonia, Exopolysaccharides (EPS) production, nitrogen fixation, and 1-aminocyclopropane-1-carboxylate (ACC) deaminase. These thirteen strains grew successfully on nutrient agar amended with NaCl up to 8%; however, the growth was reduced at a higher salinity level. Five potassium solubilizing bacteria (KSB) (L1/4, L3/3, L3/4, L4/12, and L5/1) were selected for further studies based on the highest potassium solubilization (19.16, 18.33, 17.83, 17.25, and 17.75 μg/ml), respectively under 0, 3, 5 and 7% NaCl stress. These strains were identified as Acinetobacter pittii (L1/4), Acinetobacter pittii (L3/3), Rhizobium pusense (L3/4), Cupriavidus oxalaticus (L4/12) and Ochrobactrum ciceri (L5/1).